2019
DOI: 10.46743/2160-3715/2019.3713
|View full text |Cite
|
Sign up to set email alerts
|

Stories Matter: Reaffirming the Value of Qualitative Research

Abstract: While the social sciences are experiencing narrative and emotional turns that are largely based on exploratory and theoretical qualitative research, the problematic dismissal of qualitative research approaches continues to loom large outside academia. Frequently described as a collection of “anecdotal stories,” qualitative research is dismissed as unscientific and unreliable— comments that limit the perceived usefulness of qualitative findings, especially in terms of policy reform. This article problematizes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The importance of understanding the experiences of those delivering and receiving these interventions is not to be understated and can be a vital part of enhancing the delivery of future interventions [ 54 ]. This can provide useful insights from both clinicians and patients on how to continually innovate mHealth and increase engagement and better patient care, as the value of qualitative research provides a richer insight into the lived experience [ 79 ]. This review has shown that the continents of North America, Asia, Europe, and Oceania currently have the strongest research output in support of the development of future mHealth interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of understanding the experiences of those delivering and receiving these interventions is not to be understated and can be a vital part of enhancing the delivery of future interventions [ 54 ]. This can provide useful insights from both clinicians and patients on how to continually innovate mHealth and increase engagement and better patient care, as the value of qualitative research provides a richer insight into the lived experience [ 79 ]. This review has shown that the continents of North America, Asia, Europe, and Oceania currently have the strongest research output in support of the development of future mHealth interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A single story offers an incomplete picture of an experience or event resulting in a narrative that lacks nuanced perspectives from all participants (Adichie, 2013). Even further, relying on anecdotal stories makes it easier for skeptics to dismiss qualitative methods of inquiry as just anecdotes (McAleese & Kilty, 2019). When stories are collected in a systematic way using qualitative methods and appropriate rigor, they can “…reveal a particular experience (or combination thereof) that when taken together constitute an overarching narrative message” (McAleese & Kilty, 2019, p. 823).…”
Section: The Power Of Story In Student Affairsmentioning
confidence: 99%
“…Given the challenges facing reading practitioners around the world (and the high stakes involved in this work), we see the thick description provided in this type of study as an important compliment to the extensive and critical research informing evidence-based practice in reading assessment, instruction, and remediation. “Stories are instantiations, particular exemplars, of the grand conception” (McAleese & Kilty, 2019, p. 823). These stories from the field—Jamie’s, Andi’s, and Mariah’s stories—provide a helpful exploration of how one program is working to develop and support dyslexia practitioners in the “grand conception” of teaching all children to read.…”
Section: Limitations and Implications For Future Researchmentioning
confidence: 99%